Beneath the Ice - Gansky, Alton; Copyright Paperback Collection (Library of Congress) (Barbour Pub., 2004)
When Perry Sachs, engineer/archelogist, takes a team to Antartica, he discovers secrets lurking beneath the ice, he is unaware of its full impact or of the forces intent upon reaching it. Finds an artifact hidden for thousands of years.
Keywords: Suspense fiction; Sachs, Perry (Fictitious character); Fiction; Fiction; Antarctica; Adventure fiction; Mystery fiction; Christian fiction